Molecular prevalence, subtype distribution, and zoonotic potential of Blastocystis sp. in wild rodents and shrews inhabiting Zhejiang province of China - Wang, Jiayan; Wang, Yiqing; Huang, Wenwen; Zhang, Ting; Yu, Kuai; Chen, Jiani; Zhou, Liyuting; Cao, Wenjie; Xu, Junchen; Ma, Jianshe; Huang, Huicong; Zhao, Wei (Frontiers in Veterinary Science, 2024)
Introduction: Globally, rodents and shrew populations constitute crucial elements of diverse environments and animal communities. It is imperative to study their population dynamics to mitigate any potential negative impact on humans, as they can be involved in the transmission of critical zoonotic agents, such as Blastocystis. Therefore, this study aimed to identify the prevalence and genetic composition of Blastocystis in wild rodents and shrews residing in the Zhejiang provinces of China.Methods: A total of 652 wild rodents and and shrews were captured from three different regions in Zhejiang Province from April 1st to October 31, 2023. The DNA was isolated by collecting fresh feces from the intestines of each rodent or and shrew. Rodent and shrew species were examined by vertebrate cytochrome b (cytb) analysis and PCR amplification. Blastocystis was also found in all fecal samples using PCR analysis and sequencing of the partial small subunit of ribosomal RNA (SSU rRNA) gene.Results: Among all the samples, 6.6% (43/652) showed a positive result for Blastocystis. In the results, 6 species of rodent and shrew were identified with Blastocystis, including Apodemus agrarius (n = 36) (2.8%), Niviventer confucianus (n = 75) (17.3%), Rattus losea (n = 18) (5.6%), R. norvegicus (n = 155) (2.6%), R. tanezumi (n = 86) (3.5%), and Suncus murinus (n = 282) (7.4%). The existence of 6 Blastocystis subtypes, ST4 (n = 33), ST1 (4), ST7 (n = 3), ST2 (n = 1), ST3 (n = 1), and ST5 (n = 1), were confirmed by sequence analysis.Discussion: Based on the molecular data obtained, the wild rodents and shrews under investigation were found to be concurrently infected with zoonotic subtypes of Blastocystis, including ST1 to ST5 and ST7. This suggests that these animals could potentially pose a zoonotic threat to humans and other animals susceptible to Blastocystis infection.